Гіперпролактинемічний синдром: етіологія, патогенез, клініка, діагностика, сучасне лікування - Кирилюк, М. Л. (Clinical Endocrinology and Endocrine Surgery, 2013)
The lecture presents data on epidemiology, etiology and pathogenesis, clinic, diagnostics and modern treatment of hyperprolactinemic syndrome.